Exploring the Intersection of Personality Traits and Ayurvedic Sharir Prakriti: A Comparative Study on Psychophysiological Correlates and Individual Differences - Ghate, Umesh; Indapurkar, Kavita; Patil, Sachin Rangrao; Durve, Sanjay; Khatal, Satish (Journal of Neonatal Surgery, 2025)
The study of personality is a fascinating field that has attracted researchers worldwide. Personality is defined as a dynamic and organized set of characteristics that uniquely influence an individual's cognitions, emotions, motivations, and behaviours in various situations [1]. Modern psychology has its roots in ancient Greek theories proposed by Plato, Aristotle, and Hippocrates [2]. Over time, these theories have evolved and continue to form the foundation of contemporary psychological studies [3]. Ayurveda, an ancient system of medicine, emphasizes the uniqueness of each individual through the concept of Prakriti , particularly Sharir Prakriti (physical constitution) [4]. Sharir Prakriti is determined by the predominance of the three Doshas (Vata, Pitta, and Kapha), which govern physical, mental, and emotional functions [5]. This paper aims to explore the Ayurvedic perspective on personality, focusing on Sharir Prakriti , and compare it with modern psychological theories [6].